9 The single leg squat cannot predict knee valgus in runners with patellofemoral pain syndrome. (20th December 2017) - Rees, D; MacRae, S; Younis, A
Abstract : Patellofemoral pain syndrome (PFPS) is the most common injury to befall runners and as such poses a huge barrier to exercise. Despite its prevalence, PFPS remains poorly understood and treated, with up to 90% of cases recalcitrant to therapy. An increased magnitude of knee valgus when running has been linked to patellofemoral pain syndrome, with this position proposed to increase joint contact pressure on the lateral aspect of the patellofemoral joint and cause pain. Accordingly, clinicians will commonly assess the magnitude of knee valgus when treating runners with PFPS. Accurately assessing running gait requires skill, equipment and time however, and as a consequence dynamic tests such the single leg squat are used instead. The movement patterns of the single leg squat are proposed to be similar to those when running, thus magnitude of knee valgus during a single leg squat is proposed to correlate with running knee valgus and offer some predictive value. The evidence supporting this correlation is in healthy runners only and it is unclear whether this can be extrapolated to a symptomatic population. This study aimed to investigate whether a correlation exists between knee valgus when running and performing a single leg squat in asymptomatic runners and runners with PFPS. Sixteen asymptomatic runners (asymptomatic group) and sixteen runners with patellofemoral pain syndrome (symptomatic group) were recruited. The asymptomatic group was subdivided by leg dominance and the symptomatic group was subdivided by 'painful' and 'non-painful' leg to give four distinct sub-groups. Participants were videoed performing single leg squats and running on a treadmill at a self-selected pace. Knee valgus magnitude was calculated using the frontal plane projection angle (FPPA). The strength of correlation between FPPA for running and single leg squat was calculated using Pearson's Correlation Coefficient for each of the four sub-groups. Differences in FPPA between the sub-groups for both running and single leg squat were calculated using an ANOVA and subsequent Independent T-Tests as indicated. The study found that the correlation in FPPA between running and the single leg squat was not statistically significant for the painful leg (symptomatic group (r=0.34, p=0.19)) but was for the remaining three sub-groups (p<0.05). There was no statistically significant difference in FPPA between the four sub-groups when running. Single leg squat FPPA was larger for the painful leg (symptomatic group (10.3°)) than the dominant (−0.2° (p=0.02)) and non-dominant leg (−0.4° (p=0.001)) in the asymptomatic group. This study suggests that the single leg squat cannot be used to predict the magnitude of knee valgus in runners with patellofemoral pain syndrome and refutes this current clinical practice. The significant correlation in the asymptomatic group supports previous research using this group. The lack of a statistically significant difference in running knee valgus between the sub-groups may suggest that the mechanisms for developing PFPS are not simply driven by an increased magnitude of knee valgus.